The Charm of Detail – Laces and Points in Medieval and Modern Garments - Anna Rybarczyk (Fasciculi Archaeologiae Historicae, 2020)
A good fit of clothing to the body mainly depended on the perfect cut. Another way to fit clothes to the body shape was to use lacing. In the Middle Ages, women’s gowns could be fitted with laced slits at the sides or in front of the dress. In men’s medieval attire, lacing mainly concerned the fastening of doublets and it was always placed at the front. Strings had one more special task – they supported a pair of hose tied to the doublet. In the course of time, the laces became more visible, gradually gaining a decorative function. An interesting collection of laces from archaeological excavations is stored in the Museum of Archaeology and History in Elbląg. The earliest lace is dated back to the 13th century, and another medieval find in this collection is a metal lace chape. Other artefacts are silk laces dated to the 16th, 17th and 17-18th centuries. The Elbląg collection documents the development of this part of clothing. It certainly constitutes an important part of a relatively small assemblage of surviving European fashion accessories of this type.